2018
DOI: 10.1101/416081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The biochemical properties of a novel paraoxonase-like enzyme in Trichoderma atroviride strain T23 involved in the degradation of 2,2-dichlorovinyl dimethyl phosphate

Abstract: Dichlorvos, is a broad-spectrum organophosphorus pesticide that is widely applied in the agricultural industry and considered a pollutant to fish and bees. T. atroviride strain T23, an efficient DDVP-degrading strain, could convert DDVP to dichloroacetic acid, 2,2-dichloroethanol and phosphoric acid through mineralization. RT-qPCR analysis showed TaPon1-like encoding an organophosphorus hydrolase, is continuously highly expressed in the process of degrading DDVP. TaPon1-like contained an open reading frame of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The highest activity of this enzyme was achieved at 35 °C, and the optimal pH was 8.5. The results showed that organophosphorus hydrolase provided a clue for the comprehensive understanding the mechanism underlying the organophosphorus pesticide degradation by filamentous fungi (Sun et al 2001).…”
Section: Reviewmentioning
confidence: 96%
“…The highest activity of this enzyme was achieved at 35 °C, and the optimal pH was 8.5. The results showed that organophosphorus hydrolase provided a clue for the comprehensive understanding the mechanism underlying the organophosphorus pesticide degradation by filamentous fungi (Sun et al 2001).…”
Section: Reviewmentioning
confidence: 96%